Taxonomic issues related to biological control prospects for the ragweed borer, Epiblema strenuana (Lepidoptera: Tortricidae) - Gilligan, Todd M.; Wright, Donald J.; Brown, Richard L.; Augustinus, Benno A.; Schaffner, Urs (Zootaxa, 2020)
The ragweed borer, Epiblema strenuana (Walker, 1863), has a long history of use as a biological control agent against important weed pests in the family Asteraceae. Recently, E. strenuana has been reported feeding on the invasive perennials Ambrosia confertiflora and A. tenuifolia in Israel. The geographic location of Israel has raised concern over the possibility that the moth may spread to areas such as Ethiopia where the oil-seed crop Guizotia abyssinica is cultivated, as this is a potential host for E. strenuana. However, the taxonomic status of E. strenuana and a current synonym, E. minutana (Kearfott, 1905) is unclear. These taxa have been treated as separate species in the past, and they potentially have different feeding habits and damage different parts of the plant. We analyzed DNA data and adult morphology and determined that E. minutana, stat. rev., is a valid species which we raise from synonymy with E. strenuana. Wing coloration, the shape of the female sterigma, and COI DNA barcodes are consistently different between the two species. We also determined that the species previously identified as E. strenuana in Israel is actually E. minutana. While detailed host range tests have been conducted on the E. strenuana populations released in Australia and China, the host range of E. minutana remains to be clarified. We discuss the history of biological control using E. strenuana and the implications for finding E. minutana in Israel. We also provide species redescriptions for E. strenuana and E. minutana and illustrate diagnostic characters.